Efficient biodegradation of 1, 4-dioxane commingled with additional organic compound: Role of interspecies interactions within consortia. (December 2022) - Tusher, Tanmoy Roy; Inoue, Chihiro; Chien, Mei-Fang
Abstract: Microbial consortia-mediated biodegradation of 1, 4-dioxane (1, 4-D), an emerging water contaminant, is always a superior choice over axenic cultures. Thus, better understanding of the functions of coexisting microbes and their interspecies interactions within the consortia is crucial for predicting biodegradation efficiency and designing efficient 1, 4-D-degrading microbial consortia. This study evaluated how microbial community compositions and interspecies interactions govern the microbial consortia-mediated 1, 4-D biodegradation by investigating the biodegradability and microbial community dynamics of both enriched (N112) and synthetic (SCDs and SCDNs) microbial consortia in the absence or presence of additional organic compound (AOC). In the absence of AOC, N112 exhibited 100% 1, 4-D biodegradation efficiency at a rate of 12.5 mg/L/d, whereas the co-occurrence of AOC resulted in substrate-dependent biodegradation inhibition and thereby reduced the biodegradation efficiency and activity (2.0–10.0 mg/L/d). The coexistence and negative influence of certain low-abundant non-degraders on both 1, 4-D-degraders and key non-degraders in N112 was identified as the prime cause behind such biodegradation inhibition. Comparing with N112, SCDN-1 composed of 1, 4-D-degraders and key non-degraders significantly improved the 1, 4-D biodegradation efficiency in the presence of AOC, confirming the absence of negative influence of low-abundant non-degraders and cooperative interactions between 1, 4-D-degraders and key non-degraders in SCDN-1. On the contrary, both two-species and three-species SCDs comprised of only 1, 4-D-degraders resulted in lower 1, 4-D biodegradation efficiency as compared to SCDN-1 under all treatment conditions, while max. 91% 1, 4-D biodegradation occurred by SCDs in the absence of AOC. These results were attributed to the negative interaction among 1, 4-D-degraders and the absence of complementary roles of key non-degraders in SCDs. The findings improve our understanding of how interspecies interactions can regulate the intrinsic abilities and functions of coexisting microbes during biodegradation in complex environments and provide valuable guidelines for designing highly efficient and robust microbial consortia for practical bioremediation of 1, 4-D like emerging organic contaminants. Graphical abstract: Image 1 Highlights: 1, 4-dioxane degradation efficiency of enriched and synthetic consortia were studied. Additional substrate-dependent biodegradation efficiency was observed. Biodegradation efficacy was governed by interspecies interactions within consortium. A synthetic consortium having superior biodegradation efficiency was constructed. Not all but key non-degraders were the prime contributors for efficient biodegradation.